Stress caregiver informal elderly: Can it be reduced with emotion regulation therapy? - Dimas Prastia Putra; Sri Muliati Abdullah (Jurnal Ilmiah Psikologi Terapan, 2026)
Caring for older adults places substantial physical and emotional demands on informal caregivers and may increase stress. This pilot randomized controlled trial examined whether Emotion Regulation Therapy (ERT) reduces stress and improves emotion regulation among women informal caregivers of older adults. Twenty eligible participants were randomly assigned to an experimental group (n = 10) or control group (n = 10). Stress and emotion regulation were assessed using the Perceived Stress Scale-10 and Emotion Regulation Questionnaire. Data were analyzed using Mann–Whitney U and Wilcoxon signed-rank tests. Compared with the control group, the experimental group showed significantly lower stress and higher emotion regulation at posttest and one-week follow-up. Within the experimental group, stress decreased and emotion regulation increased significantly from pretest to posttest, with improvements maintained at follow-up. These findings provide preliminary evidence that ERT may reduce stress and enhance emotion regulation among informal caregivers of older adults.